THE SIGNIFICANCE OF DEVELOPING TERMINOLOGICAL COMPETENCE IN PHILOLOGY SPECIALISTS (Scientific journal of the Fergana State University, 2024)
This article is devoted to the topic of the role and significance of terminological competence in the training of future philologists and contains detailed information on the use of terms such as competence, its content, competence, professional competence, the role of professional competence in the pedagogical process, terminological competence.